A power controller integrating MPPT and S3R topology - Wang Boxin; Liu Shufeng; Zou Jiwei; Jia Xu; Zhang Wei; Dai Lu (Dianzi Jishu Yingyong, 2025)
Satellite power systems using direct energy transmission have the advantages of simple circuit structure and high reliability, but the solar array energy utilization rate is low. In contrast, using maximum power point tracking technology can maximize the output power of the solar array, but the control is relatively complex and there is a risk of open circuit high voltage. This article proposes a MPPT (Maximum Power Point Tracking) and S3R (Sequential Switching Shunt Regulator) fusion topology power controller, which improves the energy utilization of the solar array while ensuring the reliability of the system and avoiding the open-circuit high voltage problem of the solar array. This article introduces the system composition, mode switching method, and maximum power point tracking principle of the proposed power controller in detail, and builds a test prototype for experimental verification. The experimental results prove the correctness of the theoretical analysis.